2014
DOI: 10.1016/j.addbeh.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported impulsivity, but not behavioral approach or inhibition, mediates the relationship between stress and self-control

Abstract: Stress has been associated with poor self-control. Individual differences in impulsivity and other behavioral tendencies may influence the relationship of stress with self-control, although this possibility has not been examined to date. The present research investigated whether cumulative stress is associated with poor self-control, and whether this relationship is mediated by impulsivity, behavioral approach, and behavioral inhibition in men and women. A community sample of 566 adults (319 women and 247 men)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 70 publications
6
17
0
1
Order By: Relevance
“…The high levels of CF and MF related to the high level of EDI-2 Ineffectiveness stressing the inability to control own's life indicates that the impulsivity disorder is reinforced by feelings of inadequacy and insecurity. These data are consistent with other researches emphasizing the critical role of ineffectiveness in Eating Disorders [62,63]. The increase of Impulse Regulation subscale can be associated to cognitive and motor factors reinforcing the relationship between impulse control disorder and emotional regulation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The high levels of CF and MF related to the high level of EDI-2 Ineffectiveness stressing the inability to control own's life indicates that the impulsivity disorder is reinforced by feelings of inadequacy and insecurity. These data are consistent with other researches emphasizing the critical role of ineffectiveness in Eating Disorders [62,63]. The increase of Impulse Regulation subscale can be associated to cognitive and motor factors reinforcing the relationship between impulse control disorder and emotional regulation.…”
Section: Discussionsupporting
confidence: 81%
“…Non planning impulsivity has a higher score than obese non BED but the internal analysis of BIS-11 factors show a less increase. This data is consistent with the other studies [58,59,61] underlining that the inability to think for future (non-planning) seems not to be specific of BED, but can be inserted in the spectrum of Impulse Control disorder to which BED could belong [57,[62][63][64][65][66][67]. Moreover, the high score of EDI-2 Interoceptive Awareness subscale testify the lack of body stimuli perception: specifically the ability to distinguish hunger or satiety signals.…”
Section: Discussionsupporting
confidence: 80%
“…With respect to problematic mobile phone use, Khang found that compared to self-esteem and self-efficacy, self-control is the most significant predictor of pathological mobile phone use [15, 16]. Since impulsivity is an important potential contributory factor to self-control [22], several studies have shown the vital role of impulsivity in mobile phone overuse [23]. Billieux and his colleagues measured the sub-dimensions of impulsiveness and found the urgency dimension was the strongest predictor of mobile phone abuse [24].…”
Section: Introductionmentioning
confidence: 99%
“…These include unhealthy behaviors such as substance abuse (16) and physical inactivity (17). Beyond these relationships, impatience is linked to cognitive and social incompetence, inability to cope with life frustration and stress (18), and risk of mental disorders (19,20). These untoward effects associated with impatience suggest that steeper delay discounting may be negatively correlated with telomere length, a process potentially mediated by inflammatory response and oxidative stress (12,13).…”
mentioning
confidence: 99%